2010
DOI: 10.1111/j.1365-2923.2009.03582.x
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate training and career choices: an analysis of the National Physicians Survey in Japan

Abstract: Designing and providing desirable postgraduate clinical training and achieving appropriate doctor distribution are important policy issues. Appropriate policy interventions regarding a mechanism to ensure the appropriate distribution of doctors should be established and attention should be paid to expanding doctors' choices and increasing patient satisfaction and general cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…A Japanese governmental report revealed that obstetrics & gynecology, pediatrics, and anesthesiology have suffered a more severe shortage than other specialties [2]. Moreover, the decreasing tendency of doctors to choose internal medicine and surgery has accelerated [3]. …”
Section: Introductionmentioning
confidence: 99%
“…A Japanese governmental report revealed that obstetrics & gynecology, pediatrics, and anesthesiology have suffered a more severe shortage than other specialties [2]. Moreover, the decreasing tendency of doctors to choose internal medicine and surgery has accelerated [3]. …”
Section: Introductionmentioning
confidence: 99%
“…This implies that studies in a varied healthcare system would add different insight into specialty preference. Although literature from countries other than U.S.A. and U.K. are available, those studies have tended to focus on a few specific specialties [53-55], gender difference [56], graduates who have already chosen the specialty [57], or conducted with limited participants at a single medical school [55]. Therefore, large scale studies on both students and graduates with a focus on diverse specialties are needed to obtain findings more applicable to countries in which the health system is more equitable and most students enter medical school as undergraduates (directly from secondary school).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, after 6 years of medical school, there is a two year foundation programme consisting of required and elective clinical rotations [57], during which the final decision of career choice is made. Due to the absence of regulatory mechanisms to generate balanced distribution of workforce, it allows virtually any graduate to obtain the type of specialty training desired regardless of their performance during the foundation years.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained other variables from the 2010 survey. Since 2004, physicians in Japan have been required to undertake a 2-year postgraduate clinical training program [14, 15]. In this study, we use the term “resident” to signify a physician who was undergoing postgraduate clinical training.…”
Section: Methodsmentioning
confidence: 99%